An advanced and efficient asymmetric PCR method for microarray applications - Reddy Banda, Suresh; Klapproth, Holger; Smit, Nicolaas; Bednar, Sonja; Brandstetter, Thomas; Rühe, Jürgen (Frontiers in Bioengineering and Biotechnology, 2022)
The sensitivity of a PCR based biochip assay relies on the efficiency of PCR amplicons in binding to the microarray spots. The essential factor determining the sensitivity is the amount of single stranded (ss) amplicons available for biochip hybridization. Asymmetric PCR can generate ss-amplicons depending on the ratio of primers used in the amplification process, but this process is often inefficient. We report a novel variant of PCR called the Asymmetric Exponential and Linear Amplification (AELA) which can overcome these issues and generate large amounts of single stranded amplicons. AELA-PCR introduces an amplification strategy that makes use of both exponential and linear amplification of the target nucleic acid. This is done by specifically designed primers and choice of adequate thermal profiles. In conventional PCR with a classical thermal profile, these specifically designed primers will work normally and contribute to an exponential increase of amplicons. A designed sequence extension of one of the primers and a very specific thermal profile, will result in a situation that the extended primer will be the only functional one for amplification, resulting in a linear phase of the amplification process. That is why during this step only one of the two strands of the target is amplified linearly and no longer exponentially. The result of the whole process is an amplification product enriched very strongly in one of the two single strands of the target. These adaptions in PCR are particularly favorable where the generation of ss-DNA/RNA is required. We demonstrate the higher biochip sensitivity of AELA-PCR compared to conventional amplification methods with an example of the Staphylococcus aureus detection on a DNA oligonucleotide microarray.